EPIDEMIOLOGY OF MULTIPLE MYELOMA ACCORDING TO THE КIROV REGION POPULATION REGISTERS - A. S. Luchinin; S. V. Semochkin; N. V. Minaeva; N. M. Pozdeev; I. V. Paramonov (Онкогематология)
The aim of this study was to analyze the basic epidemiological parameters of MM in the Kirov region based on own regional population register data.Materials and methods. Five hundred and sixty-seven patients with newly diagnosed MM between 1994 and 2016 were included. The median age was 64 years (range, 29–90).  The age-standardized incidence of MM in Kirov region was 1.8 cases per 100.000/year.Results. During research period (23 years) we have the positive trend of the incidence and prevalence of MM and negative tendency of mortality every year. Our prognosis of the intensive incidence in Kirov region is 2.2–2.3  cases per 100.000 in 2017–2019  years. The 5-year overall survival rate (5y-OS) was 18 % (1994–1999);  24 % (2000–2005) and 36 % (2006–2011) respectively. The median OS was 28; 26 and 38 month respectively. The median OS for patients who diagnosed in the period 2012–2016  was not achieved. The reason for the increase in the prevalence of the disease and the reduction in mortality is the greater effectiveness of new bortezomib-containing chemotherapy regimens.Conclusion.  Аmong the Kirov region population standardized incidence of MM  is 1.8 cases per 100.000/year.  The  prevalence of MM in the Kirov region has a linear growth trend from 3 to 11 patients per 100.000 peoples within the analyzed period of observation 1994–2016. OS increased from 18 to 36 % in the period from 1994 to 2011. OS of MM patients has been increasing since 2006, due to using bortezomib-containing treatment options and autologous stem cell transplantation. In general, the 5-year OS increased from 18 to 36% in the period from 1994 to 2011.